Effects of Thermodiffusion and Chemical Reaction on Magnetohydrodynamic-Radiated Unsteady Flow Past an Exponentially Accelerated Inclined Permeable Plate Embedded in a Porous Medium - B. Prabhakar Reddy; M. H. Simba; Alfred Hugo (International Journal of Chemical Engineering)
A finite difference computational study is conducted to assess the influence of thermodiffusion and chemical reaction on unsteady free convective radiated magnetohydrodynamic flow past an exponentially accelerated inclined permeable plate embedded in a saturated porous medium of uniform permeability with variable temperature and concentration. The governing nondimensional set of coupled nonlinear partial differential equations with related initial and boundary conditions are solved numerically by using the accurate and efficient DuFort–Frankel’s explicit finite difference method. The physical features of fluid flow, heat, and mass transfer under the influence of the magnetic field, angle of inclination, plate acceleration, radiation, heat source/sink, thermodiffusion, chemical reaction, and time are scrutinized by plotting graphs and then discussed in detail. It was found that the effective magnetic field and angle of inclination tend to decline the fluid motion, whereas the reverse result is detected by increasing the porosity parameter and plate acceleration. The velocity and temperature of the fluid lessen with increasing the radiation parameter. The effect of thermodiffusion raises the fluid velocity and concentration, whereas a chemical reaction has the opposite impact. The Nusselt number increases with increasing the radiation parameter and time. Increasing chemical reaction and time causes to improve the Sherwood number. This kind of problem finds momentous industrial applications such as food processing, polymer production, inclined surfaces in a seepage flow, and design of fins.